The identification of the superior human resources in managing profitable entrepreneurs’ activities during Covid-19 pandemic in Indonesia - Sumar’in Sumar’in; Sardjana Orba Manullang; Abdul Samad Arief; Syahril Syahril; Rita Kartika Sari (Jurnal Siasat Bisnis, 2021)
Purpose: This project aimed to acknowledge the entrepreneurship program in managing human resources in the pandemic era in Indonesia. The essay to understand the entrepreneurship activities in managing human resources in the pandemic era is assumed to have a close connection with acknowledging the entrepreneurship programs in the outbreak of coronavirus 2019 in Indonesia.Methodology: A serial of online information searching and literature review sessions was conducted. After data was gathered, the analysis processing using a qualitative phenomenological approach and profound interpretations were done to see if the research question's reliability and validity were met.Findings: The existing literature on understanding the entrepreneurship program in managing human resources in the pandemic and crisis era of the Covid-19 showed that there are five entrepreneurship activities that were shown relatively significant business program in managing human resources since outbreaks 2020. Finally, we successfully outlined the five related programs as follows: 1) Creating a business crisis plan, 2) More care and services, 3) be among the community, 4) Community relations, 5) Creative thinking endure, 6) Be adjustable.   Originality: Direct insights into the entrepreneurship practices, policymaking, and academic business development are beneficial in creating the next entrepreneurship program plan, especially the strategy to manage human resources with an entrepreneurial role in the pandemic crisis.Research implication: Further project is needed to anticipate the next economic crisis and social-political changes that impacted economic development in Indonesia.